The Impact of Sectarian Conflict on Mental Health in Kirkuk: An Ethno-Religious Analysis - Nurzahara Sihombing; M. Agung Rahmadi; Rabiatul Adawiyah Nasution; Nabila Sita; Amanda Aulia Putri; Helsa Nasution; Luthfiah Mawar; Shely Shely; Nafiza Rizky Ramadhani Lubis (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
This study comprehensively analyzes the impact of sectarian conflict on mental health in Kirkuk through an ethnoreligious meta-analysis of 42 studies with a total of N=15,427 participants published between 2003 and 2023. The quantitative synthesis indicates a PTSD prevalence of 47.3% (95% CI: 44.2–50.4) among victims of sectarian conflict, with an uneven distribution across groups, where the Turkmen minority records the highest prevalence at 56.8%, exceeding Arab Sunni at 43.2% and Kurdish at 41.5%. Logistic regression analysis demonstrates that direct exposure to sectarian violence increases the risk of major depression by 3.4 times (OR=3.42, p<.001), anxiety by 2.8 times (OR=2.83, p<.001), and psychosomatic disorders by 2.5 times (OR=2.54, p<.001). Further meta-regression identifies duration of conflict exposure (β=.426, p<.001) and intensity of sectarian violence (β=.389, p<.001) as significant predictors of symptom severity. In contrast to the findings of Cummings et al. (2013) and Eltally (2019), which emphasize the general impact of conflict, this study reveals specific intergenerational trauma patterns within distinct ethnoreligious communities, with the highest transmission observed among families of sectarian massacre victims (d=0.82), while simultaneously highlighting variations in communal resilience across groups as a differential determinant of post-conflict psychosocial dynamics.